Identification of boolean functions by methods of linear algebra - Skobelev, V. G.; Speranskii, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove that the problem of identification of a Boolean function by using methods of the theory of linear spaces over finite fields is solvable.